UTILIZATION OF THE "SAYA INGIN BERTANYA" APPLICATION TO IMPROVE UNDERSTANDING OF LEARNING MATERIALS IN GRADE X SMA AL-WASHLIYAH 1 MEDAN - Nainggolan, Lidya Revalina (Jurnal Pelita Pendidikan, 2024)
The aim of this research is to measure the effectiveness of using the "Saya Ingin Bertanya" application in improving understanding of learning material in class X SMA AL-WASHLIYAH 1 MEDAN. This research uses an experimental method, which aims to determine the effect of the intervention imposed on research subjects. Data collection was carried out using several techniques, namely class randomization, pre-test and post-test, questionnaires, and monitoring application activity. Data analysis in this research involved descriptive statistical tests, independent sample t-two tests, and simple linear regression analysis. The “Saya Ingin Bertanya” application is designed to help students ask questions anonymously and get answers to their questions in real-time. The main features of this application include a question and answer forum but the identity is unknown, asking questions on topics being studied and topics to be studied, asking questions outside the learning topic and learning resources that are uploaded by the teacher and can be accessed directly by students. The results of the analysis show that there is a significant difference in increasing understanding of the material between the control group and the experimental group after the intervention. The significance value obtained (p < 0.05) shows that the difference between the two groups did not occur by chance, but was significant.